Unveiling the Determinants of Work-Related Stress in the Policing Occupation (Journal of Business Management and Accounting, 2019)
The present study attempts to provide empirical evidence on the relationship between workload, working conditions, role conflict and job stress among the Royal Malaysian Police (RMP) Personnel.  A survey among 178 RMP from six departments at one XYZ Police  District  in  Selangor  was  conducted.    Self-reported  measures  for  all  variables were used to obtain data pertaining to determinants of job stress.  Multiple regression was  employed  to  investigate  three  hypotheses  that  postulated  significant  positive relationships  between  workload,  working  conditions,  role  conflicts  and  job  stress.  The  regression  results  found  that  workload  and  working  conditions  have  positive relationships with job stress.  However, role conflict did not significantly influence job stress.  Plausible justifications for the relationships between workload and working conditions and job stress were discussed. The study provides a foundation for discussing both theoretical and managerial aspects of policing occupation.